A Practical Green Synthesis and Biological Evaluation of Benzimidazoles Against Two Neglected Tropical Diseases: Chagas and Leishmaniasis - Bandyopadhyay, Debashis; Samano, Selina; Villalobos-Rocha, Juan C.; Sanchez-Torres, Luvia Enid; Nogueda-Torres, Benjamin; Rivera, Gildardo; Banik, Bimal K. (Current Medicinal Chemistry, 2017)
Antimicrobial resistance is an ever-increasing problem throughout the world and has already reached severe proportions. Two very common neglected tropical diseases are Chagas' disease and leishmaniasis. Chagas' disease is a severe health problem, mainly in Latin America, causing approximately 50000 deaths a year and millions of people are infected. About 25-30% of the patients infected with Trypanosoma cruzi develop the chronic form of the disease. On the other hand, Leishmaniasis represents complex diseases with an important clinical and epidemiological diversity. It is endemic in 88 countries 72 of which are developing countries and it has been estimated that are 12 million people infected and 350 million are in areas with infection risk. On this basis, research on organic compounds that can be used against these two diseases is an important target. A very simple, green, and efficient protocol is developed in which bismuth nitrate pentahydrate is employed as a Lewis acid catalyst in aqueous media under microwave irradiation for the synthesis of various 2-aryl substituted benzimidazoles from aldehydes and o-phenylenediamine. Other salient features of this protocol include milder conditions, atom-economy, easy extraction, and no wastes. Nine 1H-benzimidazole derivatives (1-9) with substituents at positions 2 and 5 were synthesized and the structure of the compounds was elucidated by spectroscopic methods. The compounds were screened to identify whether they posses pharmacological activity against Chagas' disease and leishmaniasis. Compound 8 showed better activity than the control Nifurtimox against INC-5 Trypanosoma cruzi strain whereas compounds 3 and 9 have demonstrated potent leshmanicidal activity. A systematic green synthetic procedure and in vitro biological evaluation of nine 1H-benzimidazoles are described.
Keywords: Benzimidazole